The Effect of Coconut Coir and Coconut Shell Charcoal Media Thickness on Reducing the Turbidity of Excavated Well Water in Gampong Lheu Blang, Darul Imarah District, Aceh Besar Regency in 2025 - sukardi, Sukardi (Aceh Sanitation Journal, 2025)
Dug well water is often used by the community as a source of clean water, but its physical quality such as turbidity is still a problem. This study aims to determine the effect of variations in the thickness of coconut coir media and coconut shell charcoal on the reduction of turbidity of dug well water. The method used was an experiment with a Complete Random Design (RAL) with 3 media thickness treatments (2 cm, 3 cm, and 4 cm) and repeated 3 times each. Additional media in the form of gravel is used on a regular basis in each treatment. Turbidity measurements are carried out before and after filtration using a turbidimeter. The results of the study showed that there was a significant influence of the thickness of the media on the reduction of turbidity of dug well water. The thickness of 4 cm provides the most optimal results in reducing the level of turbidity. Coconut coir and coconut shell charcoal media are effectively used as natural and environmentally friendly filter alternatives to improve the water quality of dug wells.